Light weight and secure database encryption using TSFS algorithm - Manivannan, D.; Sujarani, R. (2010 International Conference on Computing, Communication and Networking Technologies, 2010)
Database security has paramount importance in industrial, civilian and government domains. Organizations are storing huge amount of data in database for data mining and other types of analysis. Some of this data is considered sensitive and has to be protected from disclosure. Challenges for security in database are increased due to the enormous popularity of e-business. In recent years, insider attacks gathered more attention than periodic outbreaks of malware. Database systems are usually deployed deep inside the company network and thus insiders has the easiest opportunity to attack and compromise them, and then steal the data. So data must be protected from inside attackers also. Many conventional database security systems are proposed for providing security for database, but still the sensitive data in database are vulnerable to attack because the data are stored in the form of plaintext only. Database encryption is the only solution for avoid the risk posed by this threat. This paper focuses on a security solution for protecting of data-at-rest, specifically protecting the sensitive data that resides in databases by using TSFS algorithm with three keys thus it provide more security for database. This algorithm improves the efficiency for executing the queries in database by encrypting only the sensitive data.